Towards High Relaxivity Magnetic Resonance Imaging Contrast Agents for use in Biomaterials - Steve Bull (2007)
High relaxivity contrast agents are of great importance in the advancement of magnetic resonance imaging diagnostics for use in biomaterials. Biomaterials that are implanted into the body, with the goal of repairing or regenerating lost or damaged tissue, need to be tracked noninvasively, over time. I have completed work using self-assembly as the mechanism to achieve both tissue regenerating materials and their use as a template for noninvasive imaging by MRI.